Religion and the global middle class: towards a new research agenda. Issue 5 (3rd September 2019) - Agbaria, Ayman K.
ABSTRACT: This essay discusses the role of religion as a central facet when researching the emerging social group – the global middle class (GMC). It is argued here that religion is a particularly relevant feature for the constitution of this social group because of the GMC's transnational and cosmopolitan character. In this essay, I will draw on several examples focused on Islamic education provision in Western, pre-dominantly Christian societies to illustrate why and how religion should become critical to our study of the GMC. The essay's central argument is that there remains a gap in research related to the role of religion in the making and practising of the GMC as a social group. I conclude by proposing a future research agenda that addresses the intersections of religion, education, and the GMC on an individual, national, and global level.